PERMAINAN PLAYDOUGH DARI TANAH LIAT UNTUK MENINGKATKAN KREATIVITAS SISWA KELAS IV SDN CIPARAY - Irwan Setiawan; Agus Ahmadi Wakih; Winarti Dwi Febrianti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
Creativity refers to a person's mental process that gives birth to new ideas or new physical forms, or a combination of the two, which then become an important part of that individual. In this research, the Classroom Action Research (PTK) method was used. According to Arikunto et al (2019), there was an increase in creativity in class IV students at SDN Ciparay in making playdough from clay. This can be seen from the increase in the average student score from 77.41 in the first cycle to 84.69 in the second cycle, which were in the good and very good categories respectively. In addition, learning results showed an increase from 72.41% learning completeness in the first cycle to 89.66% in the second cycle, with 26 out of 29 students achieving completeness. The conclusion of this research is that the use of clay, together with verbal and audiovisual stimulus support, can effectively increase the creativity of students in class IV SDN 4 Ciparay in making playdough.